Prospective Primary Teachers’ Challenges on Technology Mediated Learning in Science Classrooms - Vinta A. Tiarani (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The study aims to investigate the students’ use of technology in primary science classrooms. We employed research methods that drew on qualitative techniques such as survey instruments, students’ completed assignments, and interviews. Method: The data analysis techniques were consistent with principles of theoretical sampling shared with the grounded theory approach to qualitative research. The data from survey instruments show that students perceive technology as things that help people and include both electronic and non-electronic things. Data collection over one semester involved 24 prospective primary teachers. Results: Fifteen themes emerge from students’ completed assignments, and four major themes become evident, namely videos, experiments, models, and observation. Four major themes emerge from students’ completed assignments: videos, experiments, models, and observation. The emerging data indicates that students perceive videos as technology that can facilitate observation and experiments of science by modeling (demonstrating) how the science practices work. The students’ views on technology are not aligned with the nature of science. Novelty: This study supports the contribution of the social environment to the process of learning from others and from pre-existing culture. The findings identify that thinking and reasoning activities are mediated by cultural tools ranging from material artifacts to sign systems such as language and symbolic systems an aspect that has not been previously discussed.